Inequity in maternal health care service utilization in Gujarat: analyses of district-level health survey data - Dileep V. Mavalankar; Sarah Thomsen; Ruchi Vangani; Deepak Saxena (Global Health Action, 2013)
Background: Two decades after the launch of the Safe Motherhood campaign, India still accounts for at least a quarter of maternal death globally. Gujarat is one of the most economically developed states of India, but progress in the social sector has not been commensurate with economic growth. The purpose of this study was to use district-level data to gain a better understanding of equity in access to maternal health care and to draw the attention of the policy planers to monitor equity in maternal care. Methods: Secondary data analyses were performed among 7,534 ever-married women who delivered since January 2004 in the District Level Household and Facility Survey (DLHS-3) carried out during 2007–2008 in Gujarat, India. Based on the conceptual framework designed by the Commission on the Social Determinants of Health, associations were assessed between three outcomes – Institutional delivery, antenatal care (ANC), and use of modern contraception – and selected intermediary and structural determinants of health using multiple logistic regression. Results: Inequities in maternal health care utilization persist in Gujarat. Structural determinants like caste group, wealth, and education were all significantly associated with access to the minimum three antenatal care visits, institutional deliveries, and use of any modern method of contraceptive. There is a significant relationship between being poor and access to less utilization of ANC services independent of caste category or residence. Discussion and conclusions: Poverty is the most important determinant of non-use of maternal health services in Gujarat. In addition, social position (i.e. caste) has a strong independent effect on maternal health service use. More focused and targeted efforts towards these disadvantaged groups needs to be taken at policy level in order to achieve targets and goals laid out as per the MDGs. In particular, the Government of Gujarat should invest more in basic education and infrastructural development to begin to remove the structural causes of non-use of maternal health services.